Growth, Risk and Return on Short Debt Instrument in India with Reference to 364 Days Treasury Bills - Vishalatchy, A.; P.Vijayalakshmi, Dr. (International Journal of Engineering and Technology, 2018)
Central government has to perform more welfare activities for the sake of people. It has variousmonetary sources namely individual tax, tax levied on goods and services, and other taxes. The money collected by the government has not proven to be sufficient to discharge all its duties. Under such circumstances, it issues long term as well as short term securities to raise funds. Treasury bill is one of the short term instrumentsissued by government in the money market to fulfill its financial requirements on a short term basis. In India, Treasury bills are classified into 14 days treasury Bills, 91 days treasury bills and 364 days treasury bills. Among the treasury bills, 364 days treasury bills have more duration and investors who wish to retain their money at least for a year prefer these bills. This paper analyze  364 days  treasury bills  traded in the secondary market in terms of number, volume  and outstanding amount of trade, return and risk during the study period.